2023
DOI: 10.1093/polsoc/puac031
|View full text |Cite
|
Sign up to set email alerts
|

Employing the policy capacity framework for health system strengthening

Abstract: The policy capacity framework offers relevant analytical ideas that can be mobilized for health system strengthening. However, the employment of this framework in the health field constitutes a relevant interdisciplinary gap in knowledge. This themed issue explores the relationships between the policy capacity framework and health system strengthening, in a multidimensional and interdisciplinary way, in high-income and low–middle-income countries. This introduction unpacks the dynamic interrelationships betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…However, as these policies were being implemented, studies on P4Ps identified numerous mechanisms and unintended consequences that policy makers could not control. Themes such as the need for greater organisational capacity and other mechanisms to overcome staff demotivation and pressure caused by P4P came to be addressed extensively in research (Eijkenaar et al, 2013;Renmans et al, 2016;Saddi et al, 2023;Toonen et al, 2009). By investigating frontline staff behaviour, researchers have identified numerous "gaming and cheating" practices with P4P rules in a context of increased pressure in the work environment, generating numerous unintended consequences (Lewis, 2015;Pollitt, 2013).…”
Section: Policy Mechanisms and Pmaqmentioning
confidence: 99%
“…However, as these policies were being implemented, studies on P4Ps identified numerous mechanisms and unintended consequences that policy makers could not control. Themes such as the need for greater organisational capacity and other mechanisms to overcome staff demotivation and pressure caused by P4P came to be addressed extensively in research (Eijkenaar et al, 2013;Renmans et al, 2016;Saddi et al, 2023;Toonen et al, 2009). By investigating frontline staff behaviour, researchers have identified numerous "gaming and cheating" practices with P4P rules in a context of increased pressure in the work environment, generating numerous unintended consequences (Lewis, 2015;Pollitt, 2013).…”
Section: Policy Mechanisms and Pmaqmentioning
confidence: 99%
“…To be sure, not all studies have been focusing on impact and several studies have instead focused on the processes and mechanisms triggered by P4P/PBF (De Allegri et al , 2018; Lohmann et al , 2018; Renmans et al , 2020; Singh et al , 2021; Saddi et al , 2021a, b, 2023). This certainly helps us to better understand how these programmes work and even to some extent how context may impact its effectiveness.…”
Section: The Need For a New Comparative Research Agendamentioning
confidence: 99%
“…Despite the significant proliferation of P4P and performance-based schemes in health systems and their utilisation for wider system initiatives such as promoting universal health care, raising service quality or increasing investment in specific areas of care; the evidence of health outcome effect remains mixed (Renmans et al , 2016; Paul et al , 2018; Singh et al , 2021; Diaconu et al , 2022; Saddi et al , 2023). Moreover, the paper by Kristensen and colleagues in this special edition highlight the vast range in system design while arguing that research and literature on performance schemes often remains siloed in LMICs, MICs and HICs with little cross-over or use of comparative analysis, as also emphasised as well by two earlier special issues (Saddi et al , 2018, 2021) and a satellite session at Health Systems Global (Anselmi et al , 2020) – something we start to address in this special edition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These two fields of scholarship have rarely (if ever) been compared and combined. By adopting a policy capacity approach (Brenton et al, 2022;Saddi et al, 2023;Wu et al, 2015Wu et al, , 2018 to the study of SI, we aim to analyse the intergovernmental set of competences by which governmental organisations perform SI functions with respect to two dimensions of policy capacity: analytical and operational Lippi, 2021, 2022;Denis et al, 2022;Wu et al, 2018). We believe that such cross-fertilisation has much to offer with regard to advancing our understanding of intergovernmental relations in the social service system.…”
Section: Introductionmentioning
confidence: 99%